INTERNALISASI MERDEKA BELAJAR SEBAGAI SOLUSI DIGITALISASI DI ERA MASYARAKAT 5.0 - Muhammad Ullin Nuha; M. Jamalun Nizar; Nashrulloh Ahsan (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The aim of the research is to discuss changes in society's quality standards in both the educational and social fields which are supported by technological advances, so that an independent learning curriculum emerges. The approach to this research is qualitative and the type uses library research research methods using literature (libraries). The research results state the importance of various changes that have been caused by technological advances in the Society 5.0 era. These changes focus more on improvements, in the form of quality and improving quality. Therefore, new technology emerges to help and fulfill human needs. Therefore, the independent learning curriculum was born which provides freedom of thought and creativity in the teaching and learning process for both teachers and students.